Implementation of Experiential Marketing in Tourism Development in East Java - Lilik Indrawati; Y. Budi Hermanto; Thyophoida WS Panjaitan (Budapest International Research and Critics University, 2022)
East Java has many tourist attractions, including in Magetan, Probolinggo, Batu, Surabaya, and Lamongan. The development of tourist areas in an area can increase regional income. Therefore, a strategy is needed in developing tourism objects through good handling and management from various parties. The purpose of this study was to determine the strategy in developing tourism potential. This study is a qualitative research in which data collection through interviews to 50 informan. The data analysis technique refers to the interactive analysis model developed by Matthew B. Miles and A. Michael Huberman. Based on the results of the study, it can be said that to improve and develop the existence of tourist attractions in Magetan, Batu Probolinggo, Surabaya, and Lamongan, it is necessary to have good and harmonious support and cooperation between the government, entrepreneurs or managers, and the community in an effort to provide attractive and attractive tourist objects support by public services offered such as: cleanliness, security, comfort, availability of facilities and infrastructure, supporting facilities and infrastructure as well as services provided to visitors, because tourists come to a tourist location to be able to have a pleasant experience.